Influences of mature Pinus nigra plantations on the floristic-vegetational composition along an altitudinal gradient in the central Apennines, Italy - Allegrezza M; Pesaresi S; Ballelli S; Tesei G; Ottaviani C (iForest - Biogeosciences and Forestry, 2020)
Plantations of conifers are widespread in Europe, often occurring outside of their native range. Reduction in species richness linked to increases in altitude has been previously reported for natural forests, although there is a lack of specific studies for mature pine plantations in both the Apennines and Europe. The aim of this study was to quantify the long-term effects of the extensive Pinus nigra plantations carried out between 1900 and 1956 in protected areas on floristic richness, species composition, and ecological traits of the understorey vegetation. We compared 20 mature pine plantations selected along an altitudinal gradient (700-1700 m a.s.l.) with neighbouring deciduous natural forests dominated by Ostrya carpinifolia and Fagus sylvatica, which represent the most widespread forest types in the central Apennines. The results showed that floristic richness follows two distinct altitude trends in pine plantations and natural forests. A strong reduction in species richness with elevation was observed in the natural forests, as well as a consequent increase in the local contribution to beta diversity, with a turnover of the ecological traits of the species. Contrastingly, no significant changes in richness and beta diversity were found for pine plantations in the same altitude range. Indeed, mature pine plantations up to 1400-1500 m a.s.l. showed the presence of many heliophilous and thermophilous species that are usually distributed at lower elevation. We discuss how such pine plantations can mitigate the effect of increasing altitude which is usually observed in the natural forests, slowing down the typical diversification of the forest communities along the altitudinal gradient.